Multiculturalismo e questões identitárias na literatura maravilhosa de Salman Rushdie: um estudo de Luka e o Fogo da Vida - Vilela, Vitor Martins (2023)
This present study aims to analyze the work Luka and the Fire of Life (2010) by Indian author Salman Rushdie. The story follows Luka's quest to find the fire of life, a magical element that will save his father, the city's storyteller. It is understood that the author's literature is hybrid, presenting a blend of textual genres. In this particular work, we can identify a predominant use of the marvelous genre, although elements of fantasy and magical realism are also present in certain aspects of the narrative. The objective of this study is to explore the characteristics of these genres and demonstrate, through literary analysis, how the predominance of the marvelous is achieved. Additionally, we will investigate how the author employs the marvelous to address contemporary issues such as identity and multiculturalism in a dialogue with a young audience. From this perspective, we will explore the postmodern aspect that Salman Rushdie brings to his literature, creating a metafictional historiographical text capable of intersecting genres and history, reinventing and problematizing themes relevant to our society. For the studies related to the marvelous, we have referred to Todorov (2012), Roas (2014), Camarini (2014), Furtado (1980), among other scholars on the subject. Regarding the analyses of postmodernity, relevant works by Hall (2006, 2003), Lyotard (2018), Hutcheon (1991), and other valuable texts have been considered. Armed with these studies, we aim to contribute to the enrichment of literary analysis by exploring the studies of the marvelous and the possibilities of dialogue between this genre and postmodern theories.